Pengaruh Etos Kerja, Kecerdasan Emotional, dan Komitmen Organisasi Terhadap Kinerja Pegawai Kantor Kecamatan Panakkukang Kota Makassar - Andi Pangerang Nur Akbar; Baharuddin Semmaila; Ilham Labbase (Departement of Mathematics Education, 2023)
This research was conducted with the aim of (1) Analyzing the influence of work ethic on the performance of Panakkukang sub-district employees in Makassar City. (2) Analyzing the effect of Emotional Intelligence on the performance of Panakkukang District employees, Makassar City. (3). To provoke the influence of Performance Organizational Commitment on employees of the Panakkukang District, Makassar City. The research method used in this study is descriptive analysis and multiple linear regression analysis, with a total sample of 54 respondents. Based on the results of multiple linear regression analysis, the results show that (1). Work Ethics positively and significantly affect the performance of Panakkukang District employees in Makassar City. (2). Emotional intelligence has a positive and significant effect on the performance of employees of the Panakkukang District, Makassar City. (3). Organizational Commitment positively and significantly affects the performance of Panakkukang District employees in Makassar City.